1965
DOI: 10.1002/app.1965.070090619
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dispersion on the dynamic properties of filler‐loaded rubbers

Abstract: A study has been made of the effect of increased time of mixing carbon black in rubber on the dynamic properties of the carbon black-rubber vulcanisates. Increased time of mixing reduces the dynamic modulus and dynamic viscosity as well as the phase angle at moderate amplitudes of oscillation. The changes in dynamic properties with mixing time are shown to be associated with the dispersion of the carbon black.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

1988
1988
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(102 citation statements)
references
References 5 publications
3
99
0
Order By: Relevance
“…For instance, previous studies have shown that dimensional stability and impact strength of plastic composite materials [1][2][3][4][5], mechanical properties of rubber materials [11,12], rheological properties of sealants [13] and gloss characteristics of paper [14,15] can be controlled by changing shape/size of PCCs. Anhydrous calcium carbonate has three crystalline polymorphs: calcite, aragonite and vaterite.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, previous studies have shown that dimensional stability and impact strength of plastic composite materials [1][2][3][4][5], mechanical properties of rubber materials [11,12], rheological properties of sealants [13] and gloss characteristics of paper [14,15] can be controlled by changing shape/size of PCCs. Anhydrous calcium carbonate has three crystalline polymorphs: calcite, aragonite and vaterite.…”
Section: Introductionmentioning
confidence: 99%
“…The shear modulus of fillerreinforced rubber is strain dependent. [36] In the certain range, the shear modulus decreases rapidly as the strain increases. That is due to the collapsing of filler-filler network structure in rubber composites, commonly known as Payne effect.…”
Section: Reactivity Of 2-mercapto-1-methylimidazole Toward Styrene Bumentioning
confidence: 98%
“…In each case, the storage modulus was comparatively high and nearly constant at strains below 1%. The modulus decreased at higher strains because the filler agglomerates were broken; this effect is known as the Payne effect [16]. Thus, by varying the type and quantity of filler, one can vary the modulus behavior and Payne effect of the filled rubber.…”
Section: Cure Propertiesmentioning
confidence: 99%